IMPLEMENTASI MODEL PEMBELAJARAN INKUIRI DAN PROBLEM BASED LEARNING (PBL) TERHADAP KETERAMPILAN GENERIK SAINS BIOLOGI DITINJAU DARI KEMAMPUAN AKADEMIK SISWA - Muhamad Taofiq; Dadi Setiadi; Gito Hadiprayitno (Postgraduate, University of Mataram, 2018)
This study aims to analyze the differences of generic skills through the application of inquiry learning model and Problem Based Learning (PBL) in review of the students' different academic ability in SMAN 1 Kayangan. The type of research is quassi experiment with 2x2 factorial design. The population in this study are all students of science class X1, X2 and X3 in SMAN 1 Kayangan with sampling using purposive sampling technique, so that the samples taken are class X science 1 and class X science 2 by implementing different learning model. Data analysis technique using anakova test. Hypothesis test results obtained Fcount = 20,441 with significance level 0,000 (p <0,05) indicate there are difference of generic science skill significant between class X science 1 with mnggunakan inquiry model and kels X science 2 by using PBL learning model. Result of hypothesis test of generic science skill with applying of inquiry learning model to academic ability obtained Fhitung = 34.448 with significance level 0,000 (p <0,05) indicates the interaction of inquiry learning model and PBL toward generic science skill. Keywods: Generic skills, learning models